A Study on Perception of Digital Payments System - J. , Anand; kumar, Radhaganesh; L. , Sujatha (International Journal of Psychosocial Rehabilitation, 2020)
The demonetization ended in a great increase in digital payments. With the government initiative along with Digital India and the multiplied use of cellular technology and the internet, there is a way to exponentially boom the use of digital payments. This transformation closer to digital bills brings an advantage of greater transparency in transactions, which empowers the country’s economy. In current days, many modifications in gadgets, like digital wallets and apps, help for a smooth shift to digital payments. This paper talks about the services that the clients wish from the payment banks. It also captures how comfort/ease is assisting payment banks to extend their customer base. The role of demographics as identifying factors for customers in choosing payment banks is studied in this paper. The paper, in addition, studies the impact of a customer’s decision to choose the mode of digital payments. Payment gateways have emerged as the most massive contributor in pushing cashless and electronic bills. The surge of smartphones and net connectivity of 3G and 4G is mediated by the sturdy boom of charge gateways in India. The present study is targeted on customer preference in the direction of payment gateways and analyzes the effect of demographic variables on the use of payment gateways.